PENGARUH PELATIHAN "MODEL CROSS BOX" TERHADAP PENINGKATAN KELINCAHAN PADA ANAK UMUR 9-12 TAHUN - SISWANTOYO SISWANTOYO (Jurnal Penelitian Humaniora, 2003)
Abstract A play is the most important thing to develop the children, but will be better if the game is structure, directional and programmed. The child 9-12 year represent early to be constructed and instructed in order to achieve best prfomance, but there are must be prepare the quality of its physical. The basic quality of physical like the speed, strength and endurance, added by the quality of physical supporting like flexibility and agility. To improvement biomotoric skill especially agility element require to be strived its development. Training modify the “Cross Box Model” design by Siswantoyo to develop the agility have been trial to child 9-12 year. The research conducted experimental research with the Randomized Control group pre-testpost-test design. Sum up the sample 40 composed by 20 men and 20 women, which divided in treatment group and control group. The result showed that the modification of Cross Box model for the child 9-12 year, in the reality give  the influence to make-up of agility. At the treatment group Cross Box model man 0.75 second and women 0.71 second. Matter of this means that training modify of the Cross Box model more effective to increase agility when compared to control group man 0.24 second and women0.32 second. The happening of the improvement also can be influenced by existence of age factor, gender, body mass and fatigue. Enable also motivate factor and emotional condition from individual conducting also partake to influence the maximal agility result. Keywords: influence, training, cross-box model, agility, 9-12 year